Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD Negeri Lidah Wetan IV/566 - Melani, Hesty; Karimatul, Ana; Rosydiana, Maya (ARZUSIN, 2023)
The principal is an influential person in education, especially in improving teacher performance. Principals have a great responsibility in directing everyone around them to be more developed. The expected purpose of this research is to describe how the principal's strategy in improving teacher performance at SD Negeri Lidah Wetan IV/566 Surabaya. In this study, researchers used descriptive research methods with a qualitative approach. Data collection techniques are by means of observation, interviews and using a literature review system. The subject of this research is the principal of SD Negeri Lidah Wetan IV/566. The results of this study showed: 1) The principal's strategy in improving the performance of teachers at school are: a. Enforcing teacher discipline, b. Improving the quality of teacher behavior, c. Creating comfort for teachers. 2). Supporting and inhibiting factors for principals in improving teacher performance. 3). How to overcome obstacles in improving teacher performance. The conclusion of this study is that this research can be used as a strategy in improving the performance of elementary school teachers, and can be used as motivation in improving teacher performance.